2021
DOI: 10.3390/rs13163199
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the Variation of Hydro-Meteorological Variables in the Yongding River Mountain Area Driven by Multiple Factors

Abstract: In recent decades, strong human activities have not only brought about climate change including both global warming and shifts in the weather patterns but have also caused anomalous variations of hydrological elements in different basins all around the world. Studying the mechanisms and causes of these hydrological variations scientifically is the basis for the management of water resources and the implementation of ecological protection. Therefore, taking the Yongding River mountain area as a representative w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…$$ For the attribution analysis, as UYRB is one of the most water deficient region in China, the water consumption of the middle and lower reaches of the UYRB (GT, XSB, CT and SXL) is strongly dependent on the groundwater overexploitation, with more than 60% of the total water consumption in downstream provided by groundwater (Niu et al, 2021). According to the Grace land water storage data, the water storage of UYRB decreased by 172.5 mm (S=172.5$$ \Delta S=-172.5 $$) during 2002–2016 (Niu et al, 2021) which indicated the water storage cannot be considered as constant for the whole UYRB. Therefore, only five mountainous sub‐watersheds (CGBN, CGBD, ZJK, GS and GYT) where water storages were assumed stable during the study periods were selected for quantitatively attribution analysis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…$$ For the attribution analysis, as UYRB is one of the most water deficient region in China, the water consumption of the middle and lower reaches of the UYRB (GT, XSB, CT and SXL) is strongly dependent on the groundwater overexploitation, with more than 60% of the total water consumption in downstream provided by groundwater (Niu et al, 2021). According to the Grace land water storage data, the water storage of UYRB decreased by 172.5 mm (S=172.5$$ \Delta S=-172.5 $$) during 2002–2016 (Niu et al, 2021) which indicated the water storage cannot be considered as constant for the whole UYRB. Therefore, only five mountainous sub‐watersheds (CGBN, CGBD, ZJK, GS and GYT) where water storages were assumed stable during the study periods were selected for quantitatively attribution analysis.…”
Section: Methodsmentioning
confidence: 99%
“…$$ The relative contributions of climate change (φRC$$ {\varphi R}_{\mathrm{C}} $$) and human activities (φRH$$ {\varphi R}_{\mathrm{H}} $$) to runoff change can be calculated as follows: RHgoodbreak=R2,Simulatedgoodbreak−R2,$$ \Delta {R}_{\mathrm{H}}={R}_{2,\mathrm{Simulated}}-{R}_2, $$ RCgoodbreak=Rgoodbreak−RH,$$ \Delta {R}_{\mathrm{C}}=\Delta R-\Delta {R}_{\mathrm{H}}, $$ φRCgoodbreak=RCR,$$ \varphi {R}_{\mathrm{C}}=\frac{\Delta {R}_{\mathrm{C}}}{\Delta R}, $$ φRHgoodbreak=RHR.$$ \varphi {R}_{\mathrm{H}}=\frac{\Delta {R}_{\mathrm{H}}}{\Delta R}. $$ For the attribution analysis, as UYRB is one of the most water deficient region in China, the water consumption of the middle and lower reaches of the UYRB (GT, XSB, CT and SXL) is strongly dependent on the groundwater overexploitation, with more than 60% of the total water consumption in downstream provided by groundwater (Niu et al, 2021). According to the Grace land water storage data, the water storage of UYRB decreased by 172.5 mm (S=172.5$$ \Delta S=-172.5 $$) during 2002–2016 (Niu et al, 2021) which indicated the water storage cannot be considered as constant for the whole UYRB.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the Budyko hypothesis (Budyko, 1948) has been used to analyse regional differences in long‐term annual water and energy balance time series to identify the influence of changes on mean annual runoff and evapotranspiration. Hurst rescaling can be used to examine how changes in streamflow can be explained by variability in precipitation and evapotranspiration (see Istanbulluoglu et al ., 2012; Niu et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%